PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI YANG DIMEDIASI OLEH KOMITMEN ORGANISASI PADA RUMAH SAKIT UMUM DAERAH (RSUD) KABUPATEN BREBES - Sri Limbarwati; Fitri Lukiastuti (Magister Manajemen STIE Bank BPD Jateng, 2019)
This study aims to determinant the direct and indirect influence of leadership and organizational culture to employees’ performance with the organizational commitment as a mediator variable at the RSUD Kabupaten Brebes. The population of this study is all employee at RSUD Kabupaten Brebes, as much 87 employees. Used by sensus method, all the population becomes sample, which mean the sample is 87 RSUD Kabupaten Brebes employees’. This study used primary data and secondary data, followed by computerassisted analysis of the path analysis IBM SPSS Statistics 19. The analysis showed that the leadership and organizational culture have a positive direct influence to organizational commitment. The leadership, organizational culture and organizational commitment also have a positive direct influence to employees’ performance. While there is a positive indirect influence between leadership and organizational culture with organizational commitment as a mediator variable.